STRATEGI PEMASARAN DALAM MENINGKATKAN NASABAH PRODUK PEMBIAYAAN MURABAHAH PADA KSPPS BAITUT TAMWIL TAZAKKA - Husein Adi Negoro; Rofiul Wahyudi (Journal of Global Business and Management Review, 2021)
The purpose of this study is to investigate marketing strategies that include product, price, place, promotion in increasing customers of murabahah financing products at KSPPS Baitut Tamwil Tazakka. The population used is all members of the Tazakka KSPPS in Pekalongan. The sampling technique used is purposive sampling, one head of marketing, one head of KSPPS, and one marketing finance. Data collection techniques use interviews and data analysis techniques in three stages: reduction, data presentation, and conclusion. The findings of this study indicate that the strategy implemented by KSPPS Baitut Tamwil Tazakka for murabahah financing is effective